TINJAUAN PERANCANGAN BUKU ILUSTRASI UNTUK MENINGKATKAN EMPATI ANAK REMAJA MENGENAI SPEKTRUM AUTISME - Hamdi, Muhammad Zaidan; Karnita, Rosa (Universitas Budi Luhur, 2025)
Autism Spectrum Disorder (ASD) is a developmental disorder, especially during childhood, that affects a person’s ability to engage in social interactions, exhibit appropriate behavior, and communicate effectively. Children with ASD are often misunderstood in social environments, leading to stigma and inappropriate treatment. This study aims to explore the perceptions of society, particularly adolescents, and provide a deeper understanding while raising awareness and empathy. The research uses a mixed-method approach, incorporating surveys and interviews to gather insights and firsthand experiences from respondents, as well as a case study analysis of the illustrated book